Synthesis and in vitro Antifungal Activity of 2-Aryl-5-phenylsulfonyl-1,3,4-thiadiazole Derivatives - Alireza, Foroumadi; Mohsen, Daneshtalab; Abbas, Shafiee (Arzneimittelforschung, 1999)
The synthesis and antifungal activity of a series of 2-nitroaryl-5-phenylsulfonyl-1,3,4-thiadia- zoles (5a-e) are described. The in vitro antifungal activity of the compounds was determined against a variety of fungal strains in comparison to miconazole (CAS 22916-47-8) and flucon- azole (CAS 86386-73-4). Two derivatives (5d, 5e) showed high activity against Candida al- bicans and Candida spp. having MIC values ranging from 0.048−3.12 µg/ml, providing higher potencies than the reference drug fluconazole. Compound 5a also showed high activity against Cryptococcus neoformans (MIC < 0.048 µg/ml). The activity of this compound against Asper- gillus niger and Aspergillus fumigatus was moderate (MIC = 1.56−6.25 µg/ml), while fluconazole was inactive. Moreover, the nitroimidazole derivative 5d possessed good activity against most fungal strains in comparison to fluconazole.
Keywords: Nitrofuran; Nitroimidazole; Phenyl-1,3,4-thiadiazoles; antifungal activity, synthesis